PENGARUH TIPE KEPEMIMPINAN, MOTIVASI, DISIPLIN KERJA DAN MUTU SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI KPU-D KOTA CIMAHI PROVINSI JAWA BARAT - Febrianto Adinugroho; Josy Adiwisastra; Tjahja Supriatna; Dewi Sulistyani (Jurnal Academia Praja, 2024)
This study aims to analyze the influence of leadership style, motivation, work discipline and quality of human resources on the performance of KPU-D Cimahi City employees of West Java Province both partially and together. This research uses a quantitative approach that is explanatory in nature, namely describing the actual situation in the field based on existing facts and data. The sampling technique in this study was proportionate stratified random sampling with a sample of 195 respondents. The data analysis techniques used in this study are validity test, reliability test, F test and T test, simple and multiple linear regression. Based on the results of the study it can be concluded that there is a positive and significant influence between the performance of Cimahi City KPUD employees with leadership type (65.1%), work motivation (65.1%), work discipline (58.4%), quality of human resources (76.4%). The results of this study also show that there is a positive and significant influence of leadership type variables, motivation, work discipline, and quality of human resources together on the performance of Cimahi City KPUD employees with a percentage of 83.9%.